Benefits of an Irrigation Scheme and Its Determinants to Surrounding Peripheral Rural Communities - Masela, Zandile; Mushunje, Abbyssinia; Ngarava, Saul; Taruvinga, Amon; Tatsvarei, Simbarashe (Journal of Economics and Behavioral Studies, 2018)
The objective of the study was to identify the extent of benefits and their determinants to communities surrounding the Qamata Irrigation Scheme (QIS) in the Eastern Cape Province, South Africa. The study used a quantitative based cross-sectional survey of 197 households within a radius of 20 km from the QIS. Multiple sampling methods were utilized where the villages were randomly and the households conveniently selected. A semi-structured pre-coded questionnaire was utilized to collect the data which was analyzed using descriptive statistics and multinomial logit regression. The study identified 14 discriminant benefits ranging from job opportunities, income increment food diversification to share cropping. Sixty-two percent of the households identified less than 5 benefits, whilst 27% and 11% identified 6-10 and 11-14 benefits respectively. Determinants of a surrounding household to attain benefits were significantly influenced by the distance from the scheme, the main source of income and gender of household head (P<0.01); marital and employment status (P<0.05); and access to farm land (P<0.1). The study concludes that the level of benefit diffused to surrounding households is based on socio-economic factors. The study recommends conscientization of surrounding communities on the peripheral benefits accrued from the proximity to the QIS, achievable through awareness initiatives.